MATTER OUTFLOW FROM ACTIVE GALACTIC NUCLEI - Vilkoviskij, E.Y. (Recent Contributions to Physics, 2008)
Some problems of the theory of matter outflow from AGN in connection with the unification model of AGN are brifly discussed.